Anaphylaxis Clinical Care Pathway: Incorporating Intranasal Epinephrine (Adrenaline). - Dribin,TE; Sobolewski,B; Campbell,RL; Turner,PJ; Garvey,LH; Soar,J; Wang,J; Shaker,MS; Fox,AT; McGuire,SS; Michelson,KA; Schnadower,D; et al. (J Allergy Clin Immunol Pract, 2026)
Health care providers across settings must be trained to manage anaphylaxis by (1) removing the offending allergen if still present; (2) positioning the patient with legs elevated, and if respiratory distress is present, allow the patient to sit upright with legs extended and elevated; (3) immediately administering epinephrine (adrenaline) intramuscularly (IM) or intranasally (IN) every 5 to 15 minutes for persistent anaphylaxis; and (4) optimizing airway, breathing, and cardiovascular (ABC) resuscitation. This may include supplemental oxygen, noninvasive or invasive positive-pressure ventilation, and intravenous fluid resuscitation. For life-threatening or refractory presentations, (5) IM/IN epinephrine should be administered every 5 minutes while addressing ABC derangements; this includes aggressive intravenous fluid resuscitation for patients in anaphylactic shock. Providers may continue IM or IN epinephrine or switch to the other, as both routes are considered equally efficacious based on pharmacokinetic data. An intravenous epinephrine infusion should be prepared for patients with persistent anaphylaxis after 2 doses of IM/IN epinephrine and initiated after the third dose, or earlier at the provider's discretion. In settings without epinephrine infusions, repeat IM/IN epinephrine should be administered every 5 minutes, along with other ABC interventions, and the patient should be transferred quickly to a setting equipped to provide advanced resuscitative care.